Dizziness Handicap Inventory and Visual Vertigo Analog Scale in Vestibular Dysfunction - Grigol,Thaís Alvares de Abreu e Silva (2016)
Abstract Introduction Dizziness is one of the most common symptoms among the population, producing numerous consequences for individual's quality of life. There are some questionnaires that can trace the patient's profile and quality of life impairment from dizziness, including the Dizziness Handicap Inventory (DHI) and the Visual Vertigo Analogue Scale (VVAS). Objective This study aims to correlate the results of the DHI and VVAS in patients with vestibular dysfunction. Methods This is a retrospective study of medical records of patients treated in a medical school between 2006 and 2012. Results of the DHI and EVA were collected and subjected to statistical analysis using Pearson's correlation test with p < 0.001. The significance level adopted for the statistical tests was p 0.05. Results A total of 91 records were included in this study, 72 (79.1%) from female and 19 (20.9%) from male patients, aged 23 to 86 years, with a mean age of 52.5 years. The mean score on the DHI total was 43.9 and 5.2 points for the EVA. The result of Pearson's correlation test was 0.54. Conclusion Self-perceived dizziness measured with the Dizziness Handicap Inventory has a regular and positive correlation with the Visual Vertigo Analog Scale in patients with vestibular dysfunction. The clinical trial is registered under number UTN U1111- 1170-5065.